2010
DOI: 10.11144/javeriana.upsy10-2.asce
|View full text |Cite
|
Sign up to set email alerts
|

Adding support to cross-cultural emotional assessment: validation of the international affective picture system in a chilean sample

Abstract: The present study aimed to obtain a valid set of images of the International Affective Picture System (Lang, Bradley, & Cuthbert, 2005) –a widely used instrumentation in emotion research- in a Chilean sample, as well as to compare these results with those obtained from the US study in order to contribute to its cross-cultural validation. A sample of 135 college students assessed 188 pictures according to standard instructions in valence and arousal dimensions. The results showed the expected organization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
0
11
0
2
Order By: Relevance
“…In contrast to participants from the US [22], Spain [98,100], and Brazil [54,60], study participants from Portugal rated pictures from the IAPS with lower levels of valence. In contrast, they found that IAPS pictures had higher levels of arousal than those from the US [22] and Chile [62,64], but lower levels of arousal than those from Spain [98,100], Brazil [54,60], and India [83]. In the dominance dimension, Portuguese participants gave IAPS pictures lower ratings than US and Bosnia-Herzegovinian participants, but higher ratings than Spanish participants.…”
Section: Portugalmentioning
confidence: 91%
See 1 more Smart Citation
“…In contrast to participants from the US [22], Spain [98,100], and Brazil [54,60], study participants from Portugal rated pictures from the IAPS with lower levels of valence. In contrast, they found that IAPS pictures had higher levels of arousal than those from the US [22] and Chile [62,64], but lower levels of arousal than those from Spain [98,100], Brazil [54,60], and India [83]. In the dominance dimension, Portuguese participants gave IAPS pictures lower ratings than US and Bosnia-Herzegovinian participants, but higher ratings than Spanish participants.…”
Section: Portugalmentioning
confidence: 91%
“…In a study by Dufey et al [62], participants rated 188 IAPS pictures using valence and arousal. Results demonstrated that compared with the US normative data, the Chilean sample reported lower levels of valence and a higher level of arousal.…”
Section: Chilementioning
confidence: 99%
“…This was particularly true for the arousal and dominance dimensions—although for the latter, for the reasons addressed before. In this regard, validations of the IAPS dataset across countries have also shown different rating scores for arousal for the same set of pictures (e.g., [14, 15]). This, along with gender differences, stresses the importance of carefully selecting the target crowd.…”
Section: Discussionmentioning
confidence: 99%
“…Culture encompasses exposure to certain life situations and beliefs, leading to different emotional responses: some pictures may be perceived as more or less pleasant or unpleasant, or more or less arousing, or more controlled or in control, by certain groups than by others (Matsumoto et al, 1988;Mesquita, 2001;Mesquite & Walker, 2003;Schimmack et al, 2002). Several studies on IAPS have shown comparable psychometric behaviour and confirmed the applicability of the original normative ratings across cultures (Deák et al, 2010;Drače et al, 2013;Dufey et al, 2011;Grabovac & Deák, 2019;Huang et al, 2015;Lang et al, 1995Lang et al, -2008Lasaitis et al, 2008;Lohani et al, 2013;Moltó et al, 1999Moltó et al, , 2013Ribeiro et al, 2005;Hu et al, 2005;Silva, 2011;Verschuere et al, 2001;Vila et al, 2001), and age groups (Backs et al, 2005;Gong & Wang, 2016;Grühn & Scheibe, 2008;Keil & Freund, 2009;Pôrto, 2006;Pôrto et al, 2008Pôrto et al, , 2011Ueno et al, 2019). A boomerang-shaped distribution of ratings in the valence-arousal relationship (Bradley et al, 2001;Lang et al, 1998) was obtained in all these studies despite variability in the type and size of the sample, the number of pictures being rated and the testing procedure.…”
Section: Validation Of Iaps Stimuli: Similarities and Differences Acr...mentioning
confidence: 97%
“…The results of the Brazilian (Lasaitis et al, 2008;Ribeiro et al, 2005), Spanish (Moltó et al, 1999(Moltó et al, , 2013Vila et al, 2001), Indian (Lohani et al, 2013), Serbian and Hungarian (Grabovac & Deák, 2019) and Bosnia and Herzegovina (Drače et al, 2013) valence ratings were comparable to the US standardisation, but arousal scores were higher than the US ratings. One Chilean study showed that the emotional pictures were rated more arousing than the US sample (Dufey et al, 2011). Another study showed lower arousal ratings by the Chilean sample (Silva, 2011); the valence ratings were equivalent in both studies.…”
Section: Validation Of Iaps Stimuli: Similarities and Differences Acr...mentioning
confidence: 99%